A companion to pragmatism - Shook, John R.; Margolis, Joseph, 1924- (Blackwell companions to philosophy ;, 2006)
"A Companion to Pragmatism" provides a comprehensive and current overview of one of the most vibrant and exciting fields of philosophy today. This volume of 38 predominantly new essays demonstrates understanding of the classical figures and their philosophies, while also displaying pragmatism as a living force in philosophy, producing original thought indebted to the founders. "A Companion to Pragmatism" is unique in its depth and breadth of coverage. It is an invaluable resource for anyone wishing to learn about the history and current thought of pragmatism.